Modification of the Structural-Phase State of the Surface Layer of a Cermet Composite Under Electron Beam Irradiation in Inert Gas Plasmas; Russian Physics Journal; Vol. 59, iss. 12 - Ovcharenko V. E. Vladimir Efimovich; Ivanov K. V. Konstantin Veniaminovich; Ivanov Yu. F. Yuriy Fedorovich; Mokhovikov A. A. Aleksey Aleksandrovich; Yu Bao Hai (2017, 2017)
Title screen